2004
DOI: 10.1039/b409222h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel microfluidic immunoassay for the detection of Helicobacter pylori infection

Abstract: The miniaturization of laboratory processes offers substantial advantages over traditional techniques in terms of cost, speed, and potential for multistage automation. To date, only a few studies have reported successful microfluidics-based immunoassays, most of which rely on fluorescence detection technologies. The goal of this study was to develop a poly(dimethylsiloxane) microfluidics-based immunoassay methodology and a versatile colorimetric quantification scheme for the detection of visual colour changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
(71 reference statements)
0
31
0
Order By: Relevance
“…However, when these serological kits were tested in Asian or middle east countries, the diagnostic accuracy of these tests were found to be lower, such as reports from Chinese (Leung et al 1999) and Japanese patient populations (Miwa et al 2001). These differences may be due to some reasons, such as crossreactivity to other intestinal bacteria which vary in Lin et al (2004), andPereira et al (2010) different parts of the world, the presence of H. pylori strain heterogeneity in different geographic areas (Ito et al 1997), and varying immunological responses to antigenic proteins of H. pylori in different patient populations (Khanna et al 1998). A lot of money is being spent on purchasing diagnostic kits which may not be suitable for patients in other countries and may not be as sensitive as kits made from antigens using locally isolated H. pylori Meijer et al 1997b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when these serological kits were tested in Asian or middle east countries, the diagnostic accuracy of these tests were found to be lower, such as reports from Chinese (Leung et al 1999) and Japanese patient populations (Miwa et al 2001). These differences may be due to some reasons, such as crossreactivity to other intestinal bacteria which vary in Lin et al (2004), andPereira et al (2010) different parts of the world, the presence of H. pylori strain heterogeneity in different geographic areas (Ito et al 1997), and varying immunological responses to antigenic proteins of H. pylori in different patient populations (Khanna et al 1998). A lot of money is being spent on purchasing diagnostic kits which may not be suitable for patients in other countries and may not be as sensitive as kits made from antigens using locally isolated H. pylori Meijer et al 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…4b). The assay time was only 25 min (Gao et al 2005;Kaka莽 et al 2010;Lin et al 2004). Lin et al (2004) also employed a pressure-driven microfluidic platform for rapid detection of H. pylori.…”
Section: Miniaturized and Point Of Care Diagnostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures used for bacterial culture and antigen preparation were described previously (13,14). Briefly, H. pylori strain ATCC 49503 was cultured on Columbia agar plates containing 5% sheep blood, and the plates were incubated at 37掳C under microaerophilic conditions (5% oxygen, 85% nitrogen, and 10% carbon dioxide) for 72 h (13) Bacteria were then inoculated into brucella broth supplemented with 10% fetal bovine serum and were grown overnight with gentle shaking under microaerophilic conditions at 37掳C.…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed that >95% of the captured mouse IgG was transferred to the glass. While specific capture of several other antigens to antibodies immobilized on PDMS has been demonstrated qualitatively, 15 quantitative data of the type described above for mouse IgG is lacking in the literature dealing with complex proteins such as membrane receptor proteins. In this paper, we provide such data utilizing a biomedically relevant protein associated with the development of human cancers, namely the epidermal growth factor (EGF) receptor.…”
Section: Introductionmentioning
confidence: 99%